Black Representations of Settlement on Film: Thomasine and Bushrod. (February 2017) - Jafri, Beenash
This article develops a method for analyzing Indigenous erasure in popular film that focuses not on the representations (or lack thereof) of Indigenous peoples but on representations of settlement. Whereas much of the scholarship on Native representations in film has been concerned with Hollywood's promulgation of the "mythical Indian, " I argue that a focus on settlement—rather than on bodies—is significant in the context of the ongoing, unfinished processes of colonialism, which continue to structure life in white settler states. Cultural representations that reconfigure colonial-occupied life as settled life naturalize settler colonialism while erasing and displacing Indigenous claims to land. I illuminate this method by analyzing how the 1974 "blaxploitation Western" Thomasine and Bushrod imagines settlement. The film features a pair of lovers who are on the run from the law in America's Southwest from 1911 to 1915. Because it is a film that speaks back to historical constructions of Blackness and Indigeneity, Thomasine and Bushrod productively illuminates how representations of Indigenous erasure work in often ambiguous and contradictory ways.